Water and energy threats and opportunities - Olsson, Gustaf (IWA Publishing, 2015)
This new edition of Water and Energy: Threats and Opportunities is timely and continues to highlight the inextricable link between water and energy, providing an up-to-date overview of the subject with helpful detailed summaries of the technical literature.